Assessment of Anti-SARS CoV-2 seroprevalence in habitants of Assam (AASSHA): report of the first serosurvey in Assam - Pathak, Jyotismita; Das, Mridusmita; Siddique, Khalil (International Journal Of Community Medicine And Public Health, 2021)
Background: Today, there is a pressing need to identify the proportion of people immune to the infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) so that public health policies can be formulated accordingly for the ongoing COVID-19 pandemic. Keeping this in mind, we designed a serosurvey in Assam with aims to estimate the prevalence of infection as well as the infection to case ratio of the novel coronavirus in Assam. Methods: A total of 9 districts belonging to three different strata of districts were randomly selected for the study. In these selected districts, blood samples were collected from a sample of population and were checked for the antibodies (IgG type). Those testing reactive for the mentioned antibodies were considered to have been infected ever before the onset of the study. Results: A total of 2390 study subjects were tested for the presence of antibodies against the SARS-CoV-2. The proportion of people harboring antibodies against the infection was found to be 23.7 percent. Conclusions: The serosurvey revealed that the proportion of people having antibodies was lower than that required for attaining herd immunity levels in a population. The case to infection ratios reveal that there is a large chunk of population who didn’t know about their infection.